2018
DOI: 10.1016/j.ultsonch.2018.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of acoustic pressure fields to optimize the ultrasonic cleaning technique for cylinders

Abstract: Fouling build up is a well-known problem in the offshore industry. Accumulation of fouling occurs in different structures, e.g. offshore pipes, ship hulls, floating production platforms. The type of fouling that accumulates is dependent on environmental conditions surrounding the structure itself. Current methods deployed for fouling removal span across hydraulic, chemical and manual, all sharing the common disadvantage of necessitating halting production for the cleaning process to commence. Conventionally, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…When we compared the sizes of the cleaning area, model D had the largest cleaning area of 100.83 cm 2 , which increased up to 39.65% compared to model A which cleaning area was 72.20 cm 2 , and larger than model B as well. From Figures 7 and 8, the acoustic pressure distribution indicated that the design of the UCT and transducer position did affect acoustic pressure distribution and cleaning area, consistent to the report in [14][15][16][17][18][19]. Actually, if we relocated some transducers to the side as in the study [17][18][19], we would get a larger cleaning area and higher acoustic pressure than in this study.…”
Section: Validation and Hra Approachsupporting
confidence: 85%
See 1 more Smart Citation
“…When we compared the sizes of the cleaning area, model D had the largest cleaning area of 100.83 cm 2 , which increased up to 39.65% compared to model A which cleaning area was 72.20 cm 2 , and larger than model B as well. From Figures 7 and 8, the acoustic pressure distribution indicated that the design of the UCT and transducer position did affect acoustic pressure distribution and cleaning area, consistent to the report in [14][15][16][17][18][19]. Actually, if we relocated some transducers to the side as in the study [17][18][19], we would get a larger cleaning area and higher acoustic pressure than in this study.…”
Section: Validation and Hra Approachsupporting
confidence: 85%
“…In the case which cleaning fluids flow in the UCT, when the flow rate increases, the bubble collapsing rate drops along with the cavitation [13]. The transducers' position also affects cleaning performance; if the transducers are placed in a suitable position, the cleaning performance will be high [14][15][16][17][18][19]. In order to design a UCT with high cleaning performance, computer simulation was applied to find the cause of why the UCT in this industrial factory was not cleaning properly.…”
mentioning
confidence: 99%
“…Previous work has shown capabilities to remove inner wall pipe fouling noninvasively using ultrasounds [13][14][15][16]. This is carried out by the attachment of a High-Power Ultrasonic Transducer (HPUT) onto the outer wall of a water-filled pipe.…”
Section: Fouling Removalmentioning
confidence: 99%
“…Due to the cyclic behaviour of the wave propagation, the formed bubble would increase and decrease in radius before imploding. [12] From Figure 3, the bubble increases in radius when the pressure is heading to maximum negative pressure from maximum positive pressure (rarefaction) and decreases in radius when the pressure is heading to maximum positive pressure from maximum negative pressure (compression). Compression of the bubble can cause it to burst (adiabatically) which produces pressure of up to 50MPa and temperature up to 5000K [9].…”
Section: Ultrasonic Cavitationmentioning
confidence: 98%
“…Therefore, the effect of cavitation bubbles should be captured in the simulation instead by considering ultrasound attenuation coefficient and sound speed reduction. Other limitation includes inability to obtain response concerning instantaneous pressure increase from bubble implosions [12].…”
Section: Ultrasonic Cavitationmentioning
confidence: 99%